2015
DOI: 10.1071/an13378
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical profiles and physicochemical parameters of beef from cattle raised under contrasting feeding systems and pre-slaughter management

Abstract: Diet and pre-slaughter stress are key factors that may affect the biochemical processes during conversion of muscle into meat. The aim of the present study was to evaluate the effect of two different pre-slaughter stress managements (PSM) at a slaughterhouse in Angus steers raised and finished in two contrasting feeding systems (FS grain and pasture systems), on the peri mortem muscle metabolism, and its relation to of meat quality. Results obtained showed that a higher level of pre-slaughter stress increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The pH 45min value of the PG group was significantly lower than that of the M group ( p < 0.01). Pasture‐grazed animals are less accustomed to narrow space, which leads to preslaughter stress (Pighin et al, ). After 24 hr, the pH value decreased to 5.6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH 45min value of the PG group was significantly lower than that of the M group ( p < 0.01). Pasture‐grazed animals are less accustomed to narrow space, which leads to preslaughter stress (Pighin et al, ). After 24 hr, the pH value decreased to 5.6.…”
Section: Resultsmentioning
confidence: 99%
“…Pasture-grazed animals are less accustomed to narrow space, which leads to preslaughter stress (Pighin et al, 2015). After 24 hr, the pH value decreased to 5.6.…”
Section: Feeding Regimen and Meat Qualitymentioning
confidence: 99%
“…Gruber, Tatum, Engle, Chapman, Belk and Smith (2010) also found that cattle with more excitable temperaments and higher flight scores were correlated with higher Warner Bratzler shear force (WBSF) values. Similarly, Pighin et al (2015) found that loin hardness was greater in cattle under conventional immediate pre-slaughter handling compared to reduced stress handling.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 93%
“…Most recently work by Stewart, McGilchrist, Gardner and Pethick (2014) showed that lambs have elevated plasma glucose, lactate and non-esterified fatty acid (NEFA) concentrations at slaughter, reflecting adrenergic stress resulting in increased glycogenolysis and lipolysis (Martin, McGilchrist, Thompson & Gardner, 2011). Cortisol is one of the most common stress indicators measured (Shaw & Tume, 1992) and has been shown to be elevated above basal at slaughter (Pighin et al, 2015;Probst, Spengler Neff, Hillmann, Kreuzer, Koch-Mathis & Leiber, 2014). Increases in circulating creatine kinase (CK) and aspartate aminotransferase (AST) can be seen with unaccustomed exercise, transport handling stress and low-level trauma or bruising (Fisher et al, 2010;Pettiford et al, 2008;Sutherland, Bryer, Davis & McGlone, 2009;Tarrant, 1990;Tollersrud, Baustad & Flatlandsmo, 1971).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Exposure to pre-slaughter stress leads to an increase in some stress indicators in the blood such as glucose, lactate, cortisol [8]. Cortisol is a well-known indicator of animal welfare at slaughter [9], which is elevated above basal levels during adverse situations at pre-slaughter [10,11]. Exposure to stress activates the Hypothalamic-Pituitary axis (HPA) and results in the release of catecholamines and glucocorticoids thus activating liver glycogenolysis and elevating the levels of blood glucose [9,12].…”
Section: Introductionmentioning
confidence: 99%